The impact of basic pension for urban and rural residents on the subjective well-being of the older adult in Chinese rural areas - Yang, Jianhai; Li, Ziying; Zhang, Jiexin; Zang, Zheng (Frontiers in Public Health, 2024)
Introduction As an important component of the social security system, basic pension insurance for urban and rural residents is expected to improve the quality of life of rural older adult people and make their lives better and happier. This article mainly studies the relationship between the basic pension for urban and rural residents and the subjective well-being of older adult people in rural China. Methods This paper uses data from the China Health and Retirement Longitudinal Study (CHARLS) for the years 2018 and 2020. It selected samples of rural older adult people aged 60 and above, ultimately obtaining 9,310 samples. The impact of the basic pension for urban and rural residents on the subjective well-being of rural older adult people was estimated by constructing Ordinary Least Squares (OLS) estimation methods and ordered logistic regression models. The robustness of the results was verified by changing the regression methods, and the samples were divided into different groups for heterogeneity analysis according to three different standards. Results The results show that the basic pension for urban and rural residents significantly improves the life satisfaction of rural older adult, reduces their degrees of depression, and thereby enhances their subjective well-being. The impact of the basic pension for urban and rural residents is more significant for older adult individuals in areas with a higher gender ratio, those suffering from chronic diseases, and those in the eastern regions of the country. Further verification indicates that the basic pension for urban and rural residents enhances the subjective well-being of the rural older adult by improving their health status and reducing their labor supply. Discussion Most of the existing research on basic pension insurance for urban and rural residents and subjective well-being has been conducted from the perspective of whether individuals are enrolled in the pension scheme or whether they received a pension. However, there are few studies analyzing from the perspective of the amount of pension benefits received by residents. The results of this study help to enrich the research perspective on the basic pension insurance system for urban and rural residents in China and expand the understanding of the impact and value of the basic pension for urban and rural residents.